On the Baker-Akhiezer function in the AKNS scheme - Kamchatnov, A. M. (Iop Publishing Ltd, 2001)
Expressions for the Baker-Akhiezer function and their logarithmic space and time derivatives are derived in terms of the matrix elements of U - V matrices and 'squared basis functions'. These expressions generalize the well known formulas for the KdV equation case and establish links between different forms of the Whitham averaging procedure.